The Development of Home Automation with Anti-Electricity Theft Detection System: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Television and other electrical devices have remote controls, which has made their lives much easier. The study aims to build a home automation system with an electricity theft detection system that can provide excellent quality while preserving desired control over home appliances and human presence. The researchers employed quantitative research to develop the project, and proponents should follow the SDLC prototyping process. It also comprises the research instruments used for data collecting, the validity and reliability of the instruments, data analysis methodologies and processes, and ethical concerns applied in data gathering.
Keywords: Electricity usage; Electricity Theft Detection System; Home Automation